2017
DOI: 10.1051/matecconf/201710002025
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Multiple Traveling Salesman Problem Based on Simulated Annealing Genetic Algorithm

Abstract: Abstract. It is very effective to solve the multi variable optimization problem by using hierarchical genetic algorithm. This thesis analyzes both advantages and disadvantages of hierarchical genetic algorithm and puts forward an improved simulated annealing genetic algorithm. The new algorithm is applied to solve the multiple traveling salesman problem, which can improve the performance of the solution. First, it improves the design of chromosomes hierarchical structure in terms of redundant hierarchical algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The input latitude and longitude data of the robot car ( , ) and the target point ( , ), which were received from the GPS, were used in equation 12 to get ∅ (the angle of the target point against the exact north). Then we deducted H, the heading direction (see equation 13), to get the direction error , which was the angle between the current direction and the target point. We then used the proportional control to multiply (the gain used for servo proportional control; p = 0.161) after adding c (the center angle of the servo motor for the steering) to obtain θ (that is, the command sent to the servo motor for moving).…”
Section: Experimental Vehiclementioning
confidence: 99%
“…The input latitude and longitude data of the robot car ( , ) and the target point ( , ), which were received from the GPS, were used in equation 12 to get ∅ (the angle of the target point against the exact north). Then we deducted H, the heading direction (see equation 13), to get the direction error , which was the angle between the current direction and the target point. We then used the proportional control to multiply (the gain used for servo proportional control; p = 0.161) after adding c (the center angle of the servo motor for the steering) to obtain θ (that is, the command sent to the servo motor for moving).…”
Section: Experimental Vehiclementioning
confidence: 99%
“…The maximum number L and minimum number of cities that each salesman should visit K were defined and limited to solve MTSP instances using the TSPLIB. Furthermore, Mingji Xu et al [11] used a hybrid genetic algorithm (GA) and simulated annealing (SA) to solve MTSP, enhancing the local search ability to achieve a better global optimal solution than could be obtained using a general GA; however, the solution was proven not to be the best in later research. Using ACO and GA to solve MTSP problems may not always yield consistent solutions even under exactly the same initial test setting, and each case must be tested continuously to converge the best solution.…”
Section: Related Workmentioning
confidence: 99%
“…Per (8,9), all the targets are entered and exited by the car, and per (10), each car must visit at least one target. Finally, (11) prevents the problem of a sub-path that does not include the original point. This is an NP-Hard problem, and heuristic algorithms are always adopted to solve this type of complicated optimization problem.…”
Section: Design and Principle Of Path Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various modifications were done to improve the performance of the SA algorithm. Several studies about the modification of the SA algorithm can be found in some references [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%